Pelatihan Penggunaan Online Shop Dalam Implementasi Peningkatan Skill Berwirausaha Mahasiswa FKIP-UISU: Pelatihan Penggunaan Online Shop Dalam Implementasi Peningkatan Skill Berwirausaha Mahasiswa FKIP-UISU - Melinda Siregar; Siti Aisyah Nasution Siti (Cv. Utility Project Solution, 2022)
Technological developments are now increasingly advanced, even all activities have been done online so there is no need Again, sales and purchases transactions are carried out face-to-face especially during the covid 19 pandemic. Even though it has subsided the covid 19 outbreak is still face-to-face meetings are still on reduce. to take advantage of this situation many people who open an online shop, online shop for now is quite a lot people are interested in because they don't need to go into the field enough with smartphones and internet networks they can search what they need. The use of smartphones is very help housewives in marketing their products online.In doing business, one of the important factors What must be considered is technological progress and creativity entrepreneurs in marketing them in online shops. Media Electronic marketing has been widely applied by the public to support buying and selling activities and product sales, wrong One is through digital marketing. Online Shop Usage Training In the Implementation of Increasing Student Entrepreneurial Skills FKIP-UISU will assist participants/students in marketing products using social media and e-commerce.